Social inequalities in cancer survival: A population-based study using the Costa Rican Cancer Registry - Fantin, Romain Clement (2020)
Background: Social inequalities in survival after cancer diagnosis have been described in several high-income countries, all cancer sites combined and for several specific cancer sites. The objective of this study was to analyze 5-year net survival after cancer diagnosis in a middle-income country (Costa Rica), according to the characteristics at the district level. Methods: Costa Rican Cancer Registry is a national population-based registry. All cases diagnosed between January 1, 2011 and December 31, 2015 were included (N = 46,904). Deaths that occurred before December 31, 2018 were identified. An ecological study was implemented. The 477 districts were described using the 2011 Census. Urbanity and wealth was assessed. Socioeconomic inequalities in cancer survival were measured using multivariable flexible parametric models. Life tables by socio-economic status were used. Results: 5-year net survival ranged from 9% for liver cancer to 98 % for in situ cervical cancer. Patients living in socioeconomically disadvantaged districts experienced poorer cancer survival at 5 years, after taking into account the inequalities in survival in the general population (HR = 1.23, p < 0.01). This result was robust and was found at 1, 2 and 5 years, in all-cancer combined, and in low-, medium- and high-lethality cancers. There was no difference according to the area, except for low-lethality cancers at 1 year. Discussion: Despite its universal and solidarity-based health system, Costa Rica is experiencing social inequalities in survival after cancer diagnosis